2021
DOI: 10.1093/police/paab052
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to organizational stressors and health outcomes in a sample of Italian local police officers

Abstract: Exposure to organizational stressors is known to negatively affect police officers’ well-being in terms of mental and physical health and performance. In this study, we adopted the Health and Safety Executive’s Management Standards to identify specific associations between organizational stressors and health outcomes in a sample of local police officers employed in an Italian municipality (N = 111). Compared with benchmark data, participants were exposed to high risks in six out of seven organizational dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…We investigated the associations between exposure to the seven organizational stressors of the HSE Management Standards framework, and a range of psychosomatic complaints among nurses in a medium-sized city hospital in northeastern Italy. Consistent with previous research, our results revealed significant associations between various organizational stressors and the prevalence of psychosomatic complaints [26] , [27] . Specifically, the Relationships factor emerged as a significant predictor of several psychosomatic complaints, including palpitations, irritability, anxiety, physical and mental tiredness, and headache.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We investigated the associations between exposure to the seven organizational stressors of the HSE Management Standards framework, and a range of psychosomatic complaints among nurses in a medium-sized city hospital in northeastern Italy. Consistent with previous research, our results revealed significant associations between various organizational stressors and the prevalence of psychosomatic complaints [26] , [27] . Specifically, the Relationships factor emerged as a significant predictor of several psychosomatic complaints, including palpitations, irritability, anxiety, physical and mental tiredness, and headache.…”
Section: Discussionsupporting
confidence: 92%
“…For this purpose, the HSE has developed the HSE-Management Standards Indicator Tool (HSE-MS IT) questionnaire [21] . Several studies have already demonstrated its robust psychometric properties [22] , and how each scale is sensitive to different psychological and physical outcomes, including job satisfaction [23] , [24] , perceived stress at work [25] , job-related anxiety and depression, musculoskeletal pain, hypertension and gastrointestinal disorders [26] , [27] , and work ability [28] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies have shown a connection between poor mental health outcomes in police officers and organizational stressors like long working hours, job pressure, and a lack of support. This underscores the necessity of stressorfocused interventions to protect officer wellbeing and organizational efficacy (Marcatto et al, 2021;Sullivan et al, 2022). Furthermore, the significance of coordinating HR strategies with career development initiatives for the best results is highlighted by the beneficial effects of developmental HR practices on career self-management and organizational citizenship behavior, which are mediated by transformational leadership and moderated by perceived organizational support (Purba & Demou, 2019).…”
Section: Mediating Role Of Career Developmentmentioning
confidence: 99%
“…As perceptible work stressors, job demands may consume resources in the process of employees’ coping, which may also bring more stress and form a loss helix [ 16 ]. Some studies divide the stressors of the police officers into stress from operation and stress from organization[ 20 ], The police officers are accompanied by operational risks due to the high risk of their posts, and the stress from operations is related to the special duties of the police[ 21 ]. In terms of organization, under China’s police management system, “unified leadership and hierarchical management” has enabled public security organs to undertake many tasks outside their functions, and they are also facing double assessment standards and indicator stress.…”
Section: Introductionmentioning
confidence: 99%